SYNTHETIC MEASUREMENT USED AS ASSESSMENT OF SPATIAL DISPARITIES OF THE NATURAL ENVIRONMENT - Przybytniowski, Jarosław Wenancjusz; Dziekański, Paweł (Management and Administration Journal, 2020)
One of important factors of attractiveness of a region is its natural environment, namely a set of natural elements which are of interest to a tourist. In terms of economy, it is a source of raw materials and energy, it ensures geographical space, business opportunities and a place to live and relax. The aim of the research included in this article is to indicate the possibility of using synthetic measurement to recognize spatial disparities of the natural environment on the basis of selected diagnostic features of 102 municipalities of the Świętokrzyskie Voivodeship. The data presented in this article refer to 2009, 2012 and 2015 and come from the Local Data Bank. The following variables were selected: the total use of household water per one inhabitant, the distribution network per 100 km2 - water pipe system, the distribution network per 100 km2 – sewage system, woodland area, areas protected by law, protected monuments. The elements indicated refer to entities which function and operate in a territorial unit. The methods presented enable us to identify areas of human life (or human impact on the environment) of higher/lower efficiency (which depends on the level of synthetic measure) and, then, programme their support from public funds within the framework of the regional policy.